Little elephants - Base, Graeme (New York : Abrams, 2012)
When a family's wheat crop is threatened by locusts, tiny flying elephants come to the rescue.
2.3
K-3.
K-3
Keywords: Elephants -- Juvenile fiction; Farm life -- Juvenile fiction; Magic -- Juvenile fiction; Elephants -- Ficton; Farm life -- Fiction; Magic -- Fiction; Elephants -- Ficton; Farm life -- Fiction; Magic -- Fiction; Picture books for children